Groundwater Potential Assessment in the Semarang-Demak Basin Using Geospatial and Multi-Criteria Analysis - Ardiyanto, Ruki; Ratnasari, Dian; Santosa, Budi Heru; Anisah, Anisah; Hidayat, Wahyu; Gita Alamanda Sapan, Elenora; Priyadi, Hari; Purwana, Rachmadhi (LIMNOTEK Perairan Darat Tropis di Indonesia, 2025)
Groundwater is a critical resource for meeting the increasing demands of urban, agricultural, and industrial sectors. However, overexploitation and contamination pose significant threats to its sustainability. This study aims to assess the groundwater potential zones (GWPZ) within the Semarang-Demak Groundwater Basin, a rapidly urbanizing region in Central Java, Indonesia, where clean water availability faces mounting challenges. A geospatial approach integrating Geographic Information Systems (GIS), Remote Sensing (RS), and the Analytical Hierarchy Process (AHP) was employed to identify and classify GWPZ. Key factors analyzed include geology, lithology, slope, soil type, drainage density, rainfall, geomorphology, and land use/land cover. The results delineate the basin into five classes of groundwater potential zones, ranging from very poor to very good, offering actionable insights into areas optimal for groundwater recharge and extraction. Validation using groundwater table measurements from 71 infiltration wells confirmed a significant correlation between predicted zones and observed water levels. The results showed that zones with very high groundwater potential are concentrated in the central part of the basin, primarily due to favorable conditions such as high rainfall, alluvial formations, and low drainage density. These findings provide actionable insights for stakeholders to implement targeted groundwater management strategies, ensuring sustainable water resource utilization in the face of growing urbanization and environmental pressures.